An audit of caesarean section rate based on Robson’s ten group classification system - Jose, Jishma; Arumugam, Sendhil Coumary; Habeebullah, Syed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Caesarean section (CS) rates are rising worldwide and is a major public health concern. There is lack of evidence supporting the maternal and neonatal benefits with the increasing CS rates. Robson’s ten group classification system serves as an initial structure with which caesarean section rates can be analysed. RTGCS helps us to analyse and allow us to bring changes in our practice. Methods: This was a hospital based cross sectional study conducted over a period of 10 months during the year 2018, which involved 1478 pregnant women, out of which 693 underwent CS, those who underwent CS were grouped according to Robson’s Ten group classification system and the data was collected and analyzed. Results: 693 women underwent CS and the overall section rate was 46.88%. Group 5 (previous LSCS) and Group 2 (nulliparous, >37 weeks, induced) contributed the maximum to the overall CS rates (33.9% and 26.3% respectively). The most common indication for caesarean section was previous LSCS (38%), fetal distress (19.2%) and meconium stained liquor (13.7%). Conclusions: Robson’s ten group classification system helps us in auditing the caesarean section rates. Group 5 and 2 contributes the maximum for caesarean section rates. Encouraging and adequate counselling for VBAC, proper training of obstetricians in CTG interpretation would reduce the caesarean section rates.